Teaching and Learning Research in Applied Linguistics: Practical Experiences and the Practice of Teaching and Learning Research based on the Concrete Example Informal Learning in Scenes: Socio-semiotics of (Heavy) Metal - Lang, Erika (Glottodidactica, 2014)
Teaching and learning research appears to be both a suitable and sustainable means to achieve an up-to-date competence for university students in applied linguistics. The understanding of and dealing with new multimodal ‘glocal’ semiotic systems and codes has thus emerged as a new core competence in that field. Since formal educational institutions still adhere to traditional contents, goals and methods, it has turned out to become necessary to focus on informal learning, especially when experienced in subcultures. This approach will lead to acquiring better sociosemiotic competences. The present contribution is based on data and results of imparting of knowledge about informal socio-semiotic learning at the university Wuppertal (Germany), using documents used advanced in seminars of German studies.